Moderating impact of environmental turbulence on business innovation and business performance - Mirza Waseem Abbas; Masood Ul Hassan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
The importance of Pakistan's Tourism sector has increased manifold due to economic activities under China Pakistan Economic Corridor (CPEC) initiative. However, it has been in crisis phase due to the influence of the war on terror and other administrative issues. This paper is an effort to analyze the impact of environmental turbulence on the relationship between Customer Relationship Management effectiveness (CRMe'), business innovation and business performance in organizations comprising tourism sector. Responses from 382 respondents were collected through a questionnaire. The analysis is done using Structural Equation Modeling (SEM) through Amos software. It is observed that all the moderating effects on hypothesized relations are statistically significant. In other words, technological turbulence and competitive intensity weaken (strengthen) the relation of CRMe' with business innovation and business performance. While, market turbulence strengthens (weakens) the said relation. The outcomes of this study will help stakeholders in understanding the market forces and their impact on innovation and business performance in a better way to prepare themselves for the varied challenges of CPEC.
Keywords: 330; CRM effectiveness; environmental turbulence; business innovation; technological turbulence; market turbulence; competitive intensity